LGBTI+ rights and the judiciary protagonism in Brazil: the LGBTIphobia is recognized as a crime: LGBTI+ rights and the judiciary protagonism in Brazil: the LGBTIphobia is recognized as a crime (Simbiótica. Revista Eletrônica, 2024)
The article discusses LGBTI+ rights in Brazil, focusing on the judgment that criminalized LGBTIphobia and in dialogue with the sociopolitical context of a government that understood the LGBTI+ agenda as an enemy of the State. Its objective is to understand, based on three factors, the role of the Federal Supreme Court (STF) in its favorable positions, especially with regard to this judgment, which equated LGBTIphobia with the crime of racism. To this end, it reconstructs a history of actions linked to the LGBTI+ issue in the high court, in parallel with parliamentary and federal executive movements under bibliographical review and documentary research. It concludes that the main factor of understanding for the STF's progressive position is the sociopolitical context experienced by the country, in a scenario of rise and installation of a government with a conservative moral profile that antagonized the recognition of these rights.
Keywords: sexual rights; racism; LGBTphobia; Brazil; STF